2021
DOI: 10.1016/j.isci.2021.102544
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking-aided identification of small molecule inhibitors targeting β-catenin-TCF4 interaction

Abstract: Summary Here we report a molecular docking-based approach to identify small molecules that can target the β-catenin (β-cat)-TCF4 protein-protein interaction (PPI), a key effector complex for nuclear Wnt signaling activity. Specifically, we developed and optimized a computational model of β-cat using publicly available β-cat protein crystal structures, and existing β-cat-TCF4 interaction inhibitors as the training set. Using our computational model to an in silico screen predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Previous studies used molecular docking to predict the binding affinity of small molecule inhibitors to protein targets implicated in PD and other diseases. 72 , 73 To the best of our knowledge, the relationship, correlation, and interaction of α‐syn and DJ‐1 in melanoma have not been explored so far, which motivated us to explore the possibility of conducting molecular docking using chemotherapeutic drugs to target our proteins of interest alone or as a complex. Among the three drugs, doxorubicin formed the more stable interaction for both proteins and the complex through α‐syn, followed by temozolomide and dacarbazine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies used molecular docking to predict the binding affinity of small molecule inhibitors to protein targets implicated in PD and other diseases. 72 , 73 To the best of our knowledge, the relationship, correlation, and interaction of α‐syn and DJ‐1 in melanoma have not been explored so far, which motivated us to explore the possibility of conducting molecular docking using chemotherapeutic drugs to target our proteins of interest alone or as a complex. Among the three drugs, doxorubicin formed the more stable interaction for both proteins and the complex through α‐syn, followed by temozolomide and dacarbazine.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been predicted that the compound UU-T01 binding to β-catenin around the residues Lys436, Arg469, and Lys508 and UU-T02 forms cation-π interactions with Arg474 and Arg515 [ 30 ]. Besides, docking studies predicted GB1874 binding to the β-catenin residues Arg469, Lys508, Asn426, Arg515, Arg474, and Arg435 [ 28 ]. Our study confirmed the salt bridge between Arg469 and CGA and the π interactions between Arg474 and Arg515 with iCRT14.…”
Section: Discussionmentioning
confidence: 99%
“…The WNT pathway inhibition could also be assessed by blocking the most downstream component, the interaction between β-catenin and T-cell factor 4 (TCF4) at the nucleus. This inhibition can be effectively achieved regardless of the mutations in the upstream components [ 28 ]. iCRT3, iCRT5, and iCRT14 effectively inhibit β-catenin–TCF4 interaction while allowing β-catenin binding with E-cadherin at the cell–cell adherens junctions, which is essential for the prevention of metastasis [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, Wu et al (60) found that pleomorphic adenoma gene like-2 (PLAGL2) has a role in promoting CRC cells by upregulating and stabilizing the level of β-catenin and promoting the translocation of β-catenin into the nucleus, and as PNU-74654 blocks PLAGL2 activity in CRC cells, it further prevents the development, progression and metastasis of CRC. GB1874 blocks Wnt signaling by targeting the β-catenin-TCF4 protein-protein interaction, thereby inhibiting xenograft tumor growth in vivo and CRC stem cell proliferation in vitro (61).…”
Section: Pnu-74654 Gb1874 and Inhibitor Of B-catenin And Tcf (Icat) P...mentioning
confidence: 99%